Comunidad LGTBI como víctima del conflicto armado en Colombia: un análisis desde la política pública LGTBI (2022)
The Colombian armed conflict and it’s associated with the LGBT community human rights violations goes together, that’s why in the middle of the armed conflict y post-conflict, as victims they have right to be due these violations, those right are: truth, justice, integral reparations, and no repetition assurance. Here goes in the scene the public policies and their scheduled actions, to be able to guarantee to the access and the enjoyment of rights, that in the case of LGBT community victims of the armed conflict, for they have a differential focus, requires a policy that requires a policy tailored to their needs. In the subject of actions with LGBT community victims of the armed conflict, are described in the action plan of public policy to guarantee the effective exercise of the rights of people who are part of the LGBTI sectors and of people with sexual orientations and diverse gender identities, in the section called “Peace and Reconciliation”. Then here it is required to do a description of those actions and realize if they are able to guarantee the right they have as victims of the armed conflict K